2013
DOI: 10.1242/dmm.011502
|View full text |Cite
|
Sign up to set email alerts
|

Pain hypersensitivity mechanisms at a glance

Abstract: There are two basic categories of pain: physiological pain, which serves an important protective function, and pathological pain, which can have a major negative impact on quality of life in the context of human disease. Major progress has been made in understanding the molecular mechanisms that drive sensory transduction, amplification and conduction in peripheral pain-sensing neurons, communication of sensory inputs to spinal second-order neurons, and the eventual modulation of sensory signals by spinal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
134
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 70 publications
2
134
0
1
Order By: Relevance
“…Although the review indicated that many of the changes that occur in the spinal cord result from alterations in the function of dorsal horn interneurons, there was little discussion of the incredible heterogeneity of the interneurons. The present review has the interneurons as its focus, hopefully building upon several excellent reviews that appeared in the last few years (Ribeiro-da-Silva and De Koninck, 2009; Todd, 2010) and others that detailed the incredible biochemical complexity of dorsal horn organization (Gangadharan and Kuner, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Although the review indicated that many of the changes that occur in the spinal cord result from alterations in the function of dorsal horn interneurons, there was little discussion of the incredible heterogeneity of the interneurons. The present review has the interneurons as its focus, hopefully building upon several excellent reviews that appeared in the last few years (Ribeiro-da-Silva and De Koninck, 2009; Todd, 2010) and others that detailed the incredible biochemical complexity of dorsal horn organization (Gangadharan and Kuner, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Neuropathic pain is brought about by damage to the nerves themselves and can be as a result of injury, disease, or environmental factors. The boundaries of nociceptive and neuropathic pain overlap and in such instances patients may suffer from pain derived from damage to both tissues and nerves (Gangadharan and Kuner, 2013).…”
Section: Painmentioning
confidence: 99%
“…The impulses in the nociceptors are conveyed to second order neurons in the spinal medulla 5456. At spinal level, the signal may be modulated, either amplified or attenuated, by different interneuronal pathways.…”
Section: Introductionmentioning
confidence: 99%